Pencegahan Korupsi Menurut Perspektif Abu Ubaid - Ginoga, Muhamad Ayul; Mursyid (Rayah Al-Islam, 2023)
Abu Ubaid's economic thoughts reflect the need to maintain and defend the rights and obligations of the community, make justice the main principle in carrying out the wheels of government policy and emphasize a sense of unity and shared responsibility. In addition, Abu Ubaid also explicitly stated that the government is obliged to guarantee a decent standard of living for every individual in a Muslim society. Abu Ubaid said that state revenues (fai', khumus, shadaqah and zakat) must be managed by the state and allocate them to the community. According to Abu Ubaid, money must have intrinsic value Alaihi Salam a standard of exchange value and AS a medium of exchange. He is of the view that only dinars and dirhams are suitable for use Alaihi Salam a medium of exchange because they have a stable value so that they can avoid the flow of inflation which is bad for the country's economy.